CONSUMPTION OF RED SPINACH AND BEETROOT JUICE TO PREVENT ANEMIA IN ADOLESCENTS AT AL- AZIZI ISLAMIC BOARDING SCHOOL IN 2023 - Daulay, Kartika; Karo, Marni BR; Manulung, Riyen Sari (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2024)
Anemia is a disease characterized by lower levels of hemoglobin (Hb) and red blood cells (erythrocytes) than normal levels. In general, this disease is suffered by many people in the world, especially in developing countries and in lower middle economic groups. One of the non-pharmacological steps taken to prevent anemia and increase iron levels is to consume red spinach and beetroot juice. Red spinach contains calories, carbohydrates, protein, fat, protein, fat, vitamins (A, B1, E, C, and folate), and minerals (calcium, phosphorus, and iron). Apart from that, the iron content in red spinach is quite high compared to other vegetables. Meanwhile, beets contain vitamins, carbohydrates, protein and fat which are useful for body health. The aim of this research is to determine the effect of giving red spinach and beetroot juice on the prevention of anemia in adolescents at the Al-Azizi Islamic boarding school. This research uses a One Group Pretest Posttest design. The sample consisted of 30 people using total sampling technique. The research was conducted from July to August 2023. Test the research hypothesis using the Wilcoxon test. The Wilcoxon test results show a p value = 0.000 p value 0.005, which means there is an influence on hemoglobin levels before and after giving Red Spinach and Beetroot Juice. There was an average increase in hemoglobin levels before and after treatment of 2.04 ± 0.2 gr/dl. It was concluded that there was a significant difference in hemoglobin levels before and after consuming red spinach and beetroot juice at the al-Azizi boarding school..